(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The development of the world web increases the online users and consequently forces many governments around the world to take advantage of the facilities offered by the internet. One of these facilities is the E-Government. Electronic government or E-government represents a major change in the culture and the practices of government works. It is considered as a source of services for companies and citizens. In order to make e-government effective, it is necessary to make some changes in the governmental operational aspects along with constructing potential technology. The e-government includes multiple types of technology. Thus, governments should exploit the benefits by investing heavily and setting deadlines on e-government projects. The aims of this paper are to examine the peoples satisfaction of the e-government services and measure the degree of public confidence in the services provided by the government. The study has shown that there is a satisfaction in general about the services provided by the government and the confidence in the service provided was to the expected limit for the reasons that we will see below.